Vpliv 9-tedenske vzdržljivostne vadbe na pehotnih ovirah (vojaškem poligonu) na razvoj specialne vzdržljivosti mladih nogometašev - Železnik, Matjaž (Šport (Ljubljana), 2017)
Training on army obstacle course has impact on the development of psychomotor skills and functional abilities as well as on the development of personal characteristics. The aim of our study was to determine the effect of such training on special soccer endurance in comparison with standard soccer specific training methods. Two groups of soccer players from NK MB Tabor U16 N=15 (experimental group - ES) and U17 N=13 (control group - KS) were tested before and after the nine-week training period. Special soccer endurance was tested with the "Running in square" test. In the nine-week training period both groups completed 32 similar intensity training sessions. 16 from 32 training sessions with ES were completed on army obstacle course. KS completed all 32 training sessions on soccer pitch with standard soccer specific training methods. ES improved its average test time for 3,3 seconds or 5,1% (p = 0,00) while KS average test time improved for only 0,18 second or 0,25% ( p = 0,05). A complex training on army obstacle course can be an important factor of psychophysical conditioning of young soccer players.
Keywords: army obstacle course training; football; mladi; nogomet; soccer; specialna vzdržljivost; specific endurance; sport; šport; trening; vojaški poligon; youth